Phát triển năng lực dạy học song ngữ cho sinh viên sư phạm theo tiếp cận CLIL: Một nghiên cứu thực nghiệm - Nguyễn Thị, Huyền; Nguyễn Thị Thanh Hồng, Nguyễn Thị Thanh Hồng; Lê Diên Phương, Lê Diên Phương (Tạp chí Giáo dục, 2026)
In the context of Vietnam implementing the policy of introducing English as a second language in schools, developing bilingual teaching competence for pre-service teachers has become increasingly urgent to meet the demands of educational reform. However, in practice, students still face limitations in using English for subject-specific instruction and lack experience in applying integrated teaching approaches. This study aims to evaluate the effectiveness of the CLIL approach using a mixed-methods design with a quasi-experimental model on a sample of 250 participants. The findings indicate that CLIL significantly enhances students’ bilingual teaching competence, particularly in integrating content and language, designing instructional materials, and organizing teaching activities in English. At the same time, the study identifies several challenges, including language anxiety, insufficient teaching materials, and limited CLIL training. The study confirms that CLIL is an effective approach in teacher education and proposes a competency framework and a bilingual teacher training model appropriate to the Vietnamese context.